Preferences, actions and voting rules - Alaitz Artabe; Annick Laruelle; Federico Valenciano (SERIEs - Journal of the Spanish Economic Association, 2012)
In this paper we address several issues related to collective dichotomous decision-making by means of quaternary voting rules, i.e., when voters may choose between four actions: voting yes, voting no, abstaining and not turning up-which are aggregated by a voting rule into a dichotomous decision: acceptance or rejection of a proposal. In particular we study the links between the actions and preferences of the actors.We showthat quaternary rules (unlike binary rules,where only two actions -yes or no- are possible) leave room for manipulability (i.e., strategic behaviour). Thus a preference profile does not in general determine an action profile. We also deal with the notions of success and decisiveness and their ex ante assessment for quaternary voting rules, and discuss the role of information and coordination in this context.
Keywords: C71; D71; 330; voting; abstention; absent voter; Abstimmungsregel; Kooperatives Spiel; Neue politische Ökonomie; Theorie